THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER VALUE ON CUSTOMER LOYALTY AT ALFAMART PULO KITON, BIREUEN REGENCY - Rahmatul Azkia; Raina Tasya Ulmi; Raihanil Jannah; Junaida; Muhammad Ferdiananda Chadafi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This study aims to analyze the influence of product quality and service quality on consumer purchasing decisions at Investor Jeunieb Clothing Store in Bireuen. The research was conducted at Investor Jeunieb Clothing Store in Bireuen. The object of the research is consumers who visit Investor Jeunieb Clothing Store. The population in this study includes all consumers of Investor Jeunieb Clothing Store, the exact number of which is unknown. The sample was taken using the Hair formula, with a total sample size of 98 respondents. This study uses a multiple linear regression analysis model to determine the effect of product quality and service quality on purchasing decisions. The data was analyzed using SPSS software version 25.0. The analysis tools used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, R-tests, and R-Square tests. The t-test results show that product quality with a t-value greater than the critical t-value at the 5% level (6.514 > 1.985) and a significance value of 0.000 < 0.05 and service quality with a t-value greater than the critical t-value at the 5% level (6.890 > 1.985) and a significance value of 0.001 < 0.05 have a significant effect on purchasing decisions. The F-test results indicate that the regression model used is significant with an F-value greater than the critical F-value (200.848 > 2.70) and a significance value (sig) of 0.000 < 0.05, which means that product quality and service quality together have a significant influence on purchasing decisions. The R-test results show a strong correlation between the independent variables and the dependent variable (R = 0.899). The R-Square test results indicate that 0.809 or 80.9% of the variation in customer loyalty can be explained by service quality and customer value, while the remaining 19.1% is influenced by other variables not examined in this study.